The Effect of Website Design Quality and Service Quality toward Repurchase Intention in the E-commerce Industry: A Cross-Continental Analysis - Nicholas Wilson; Keni Keni; Pauline Henriette Pattyranie Tan (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2019)
The purpose of this study is to examine and understand the effect of website design quality and service quality toward consumers’ repurchase intention in the Asian, European, American, and Australian e-commerce industry. This research implemented survey method, in which questionnaires were chosen as instruments for data collection. A total of 1000 questionnaires were electronically distributed to the respondents across four continents, in which a total of 869 were deemed usable. Out of 869 questionnaires, a total of 200 questionnaires collected from respondents living in the Asian continent, 189 questionnaires collected from respondents living in the American continent, 243 questionnaires collected from respondents living in the European continent, and 237 questionnaires collected from respondents living in the Australian continent. This research implemented PLS-SEM method to analyze and generate findings from the data. Based on the results generated from the analysis of the data, it could be concluded that in the Asian, Australian, and European continents, service quality played a more important and significant role in affecting consumers’ repurchase intention in the e-commerce industry compared to website design quality. In contrast, the results generated in this research also concluded that website design quality played a more important role in affecting consumers’ repurchase intention in the American e-commerce industry. Furthermore, customer satisfaction mediated the relationship between website design quality and service quality toward consumers’ repurchase intention in the Asian, Australian, European, and American e-commerce industry.